Psychological Vulnerabilities and Propensities for Involvement in Violent Extremism. (20th March 2014) - Borum, Randy; Busch, Kenneth G.; Schouten, Ronald; Weissman, Sidney H.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> Research on the psychology of terrorism has argued against the idea that most terrorist behavior is caused by mental illness or by a terrorist personality. This article suggests an alternative line of inquiry – an individual psychology of terrorism that explores how otherwise normal mental states and processes, built on characteristic attitudes, dispositions, inclinations, and intentions, might affect a person's propensity for involvement with violent extremist groups and actions. It uses the concepts of "mindset" – a relatively enduring set of attitudes, dispositions, and inclinations – and worldview as the basis of a psychological "climate, " within which various vulnerabilities and propensities shape ideas and behaviors in ways that can increase the person's risk or likelihood of involvement in violent extremism. Copyright © 2014 John Wiley & Sons, Ltd.